Magnetic Resonance Sensors (MDPI - Multidisciplinary Digital Publishing Institute, 2015)
Magnetic Resonance finds applications, from spectroscopy to imaging, on a routine basis in the majority of research and medical institutions. It is also becoming more frequently used for specific applications in which the whole instrument and system is designed for optimum operation. Magnetic Resonance sensors have been applied to fields as varied as petro-chemistry - with borehole logging, food engineering - with online process monitoring, emergency medicine - with point of care diagnostics and civil engineering - with sensors for monitoring cement drying. This great diversity is seeing exciting developments in magnetic resonance sensing technology published in application specific journals where they are often not seen by the wider sensor community.
English
Keywords: magnetic resonance; diffusion; relaxometry; spin echo; pulse sequence; relaxation time; sensor design; applications